The comparative effects of mGlu5 receptor positive allosteric modulators VU0409551 and VU0360172 on cognitive deficits and signalling in the sub-chronic PCP rat model for schizophrenia. (1st May 2022) - Brown, Jessica; Iacovelli, Luisa; Di Cicco, Gabriele; Grayson, Ben; Rimmer, Lauren; Fletcher, Jennifer; Neill, Joanna C.; Wall, Mark J.; Ngomba, Richard T.; Harte, Michael
Abstract: In schizophrenia, mGlu5 receptor hypofunction has been linked with neuropathology and cognitive deficits, making it an attractive therapeutic target. The cognitive impairment associated with schizophrenia remains an unmet clinical need, with existing antipsychotics primarily targeting positive symptoms, with weaker and more variable effects on cognitive deficits. Using the sub-chronic phencyclidine rat model, widely shown to mimic the cognitive impairment and neuropathology of schizophrenia, we have investigated two mGlu5 receptor positive allosteric modulators (PAMs), VU0409551 and VU0360172. We compared the efficacy of these compounds in restoring cognitive deficits and, since these two PAMs have reportedly distinct signalling mechanisms, changes in mGlu5 receptor signalling molecules AKT and MAPK in the PFC. Although not effective at 0.05 and 1 mg/kg, cognitive deficits were significantly alleviated by both PAMs at 10 and 20 mg/kg. The compounds appeared to have differential effects on the scPCP-induced increases in AKT and MAPK phosphorylation: VU0409551 induced a significant decrease in expression of p-AKT, whereas VU0360172 had this effect on p-MAPK levels. Thus, the beneficial effects of PAMs on scPCP-induced cognitive impairment are accompanied by at least partial reversal of scPCP-induced elevated levels of p-MAPK and p-AKT, whose dysfunction is strongly implicated in schizophrenia pathology. These promising data imply an important role for mGlu5 receptor signalling pathways in improving cognition in the scPCP model and provide support for mGlu5 receptor PAMs as a possible therapeutic intervention for schizophrenia. Highlights: mGluR5 PAMs VU0409551 and VU0360172 reverse cognitive deficits in the scPCP model. Elevated PFC p-AKT and p-MAPK expression in scPCP rats was lowered by mGluR5 PAMs. p-AKT and p-MAPK expression was reduced by VU0409551 and VU0360172, respectively.